2017
DOI: 10.1186/s12879-017-2483-9
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis screening among persons with diabetes mellitus in Pune, India

Abstract: BackgroundDiabetes mellitus (DM) increases tuberculosis (TB) risk, and there is increasing concern over the public health implications of the convergence of these two epidemics. Screening for TB among people with DM is now recommended in India.MethodsPeople with DM seeking care at a large public sector tertiary care hospital clinic in Pune, India, were screened for TB from June 2015 to May 2016. All consenting people with DM were screened for TB at each clinic visit using a five-item, WHO-recommended questionn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 18 publications
(13 reference statements)
0
30
0
Order By: Relevance
“…The algorithms for active TB will be applied as described elsewhere. 40 41 …”
Section: Methods and Analysis For Tb And Dm Researchmentioning
confidence: 99%
“…The algorithms for active TB will be applied as described elsewhere. 40 41 …”
Section: Methods and Analysis For Tb And Dm Researchmentioning
confidence: 99%
“…Tuberculosis (TB) has emerged as the most fatal infectious disease worldwide [ 1 ], and the burden of diabetes mellitus (DM) has risen steeply in low- and middle-income countries (LMICs) [ 2–4 ]. India contributes the world’s largest TB burden (>2.7 million cases in 2019) [ 1 , 5 , 6 ] and among the largest burdens of DM (77 million adults) [ 3 , 4 , 6 ]. Convergence of the TB and DM epidemics in India may impede global TB control efforts [ 7 ], as it is well accepted that DM increases the risk of TB disease [ 8–10 ].…”
mentioning
confidence: 99%
“…[16] S. Kumpatlaetal [17], screened 7083 patient of DM for TB and found that only 50(0.7%) patients had current or Past TB, which was substantially lower than what we found (5.3%). Another study by Mave et al which screened 630 patients in a public sector tertiary care hospital failed to yield any active TB case, using a WHO-recommended questionnaire among people with DM [18].A thorough screening by a Pulmonary physician, experienced in TB management could at least partly explain the higher yield in our study. There has been few attempts to…”
Section: Discussionmentioning
confidence: 50%